Population pharmacokinetics of piperaquine after two different treatment regimens with dihydroartemisinin-piperaquine in patients with Plasmodium falciparum malaria in Thailand. - Tarning, J; Ashley, E; Lindegardh, N; Stepniewska, K; Phaiphun, L; Day, N; Mcgready, R; Ashton, M; Nosten, F; White, N (2008)
The population pharmacokinetics of piperaquine in adults and children with uncomplicated Plasmodium falciparum malaria treated with two different dosage regimens of dihydroartemisinin-piperaquine were characterized. Piperaquine pharmacokinetics in 98 Burmese and Karen patients aged 3 to 55 years were described by a two-compartment disposition model with first-order absorption and interindividual random variability on all parameters and were similar with the three- and four-dose regimens. Children had a lower body weight-normalized oral clearance than adults, resulting in longer terminal elimination half-lives and higher total exposure to piperaquine (area under the concentration-time curve from 0 to 63 days [AUC day 0-63]). However, children had lower plasma concentrations in the therapeutically relevant posttreatment prophylactic period (AUC day 3-20) because of smaller body weight-normalized central volumes of distribution and shorter distribution half-lives. Our data lend further support to a simplified once-daily treatment regimen to improve treatment adherence and efficacy and indicate that weight-adjusted piperaquine doses in children may need to be higher than in adults.